Mortality in young adult patients with acute ischaemic stroke. (11th January 2020) - Schneider, Siim; Vibo, Riina; Taba, Nele; Kõrv, Janika
Abstract : Objectives: This study aimed to determine short‐ and long‐term mortality, clinical determinants and causes of death in young patients with ischaemic stroke. Materials and Methods: We performed a hospital‐based study of 18‐ to 54‐year‐old consecutive patients with ischaemic stroke, who were treated in the two largest hospitals in Estonia from 2003 to 2012. All cases were reviewed by the authors. Survival data and causes of death were obtained from the Estonian Population Registry and the Causes of Death Registry, respectively. Logistic regression and Cox proportional hazard models with backwards stepwise analysis were used to identify determinants of mortality. Results: We identified 738 patients, of whom 124 died during the 5‐year follow‐up. Cumulative mortality rates at 30 days and 5 years were 4.5% (95% confidence interval [CI], 3.0%‐6.0%) and 16.8% (95% CI, 14.1%‐19.5%), respectively. The proportion of deaths due to vascular causes was 87.9% at 1 month and 54.6% at 5 years. Thirty‐day mortality was independently associated with severe stroke, with a National Institutes of Health Stroke Scale (NIHSS) score >15, and post‐stroke infections. The determinants of 5‐year mortality were post‐stroke infections, structural cardiac diseases and moderate stroke severity with NIHSS score of 7‐15. Conclusion: The mortality rate among young patients with ischaemic stroke in Estonia is higher than that reported in previous studies and is associated with increased stroke severity, post‐stroke infections and structural cardiac diseases. These results emphasize the need for more effective preventive strategies in these patient groups.